Molecular characteristics and taxonomic status of morphologically similar barnacles (Amphibalanus) assessed using the cytochrome c oxidase 1 gene - Sri Riani; ROMANUS EDY PRABOWO; Agus Nuryanto (Society for Indonesian Biodiversity, 2021)
Abstract. Riani S, Prabowo RE, Nuryanto A. 2021. Molecular characteristics and taxonomic status of morphologically similar barnacles (Amphibalanus) assessed using the cytochrome c oxidase 1 gene. Biodiversitas 22: 1456-1466. Amphibalanus variegatus and A. reticulatus have similar external morphology. Morphological similarities can be a severe problem for direct species-level identification. The problem can be overcome through anatomy-based identification and validated through molecular barcoding. Molecular characterization using the cytochrome c oxidase 1 (COI) gene provides a useful tool for precise species identification. This study attempted to assess the molecular characteristics of morphologically similar barnacle (Amphibalanus) specimens collected at five localities in Indonesia to validate their taxonomic status. Forty-five barnacle specimens were collected during the field trips in Lampung, Jakarta, Semarang, Bali, and Lombok. The COI gene was amplified using LCO1490 and HCO2198 primers. The gene was sequenced using bidirectional sequencing at 1st base Asia. The specimens' taxonomic status was determined based on sequence identity, genetic distance, monophyly, nucleotide compositions, and nucleotides in a particular position. Shell shapes-based identification placed barnacle specimens into A. reticulatus. However, anatomical-based identification placed barnacle samples into two different anatomic groups, which was further validated by molecular data that two anatomic groups of Amphibalanus samples have significant differences in their COI gene. Based on the molecular characteristics, 43 samples were identified as A. reticulatus, while the two remaining samples were identified as A. variegatus.